1993
DOI: 10.1080/00288233.1993.10427481
|View full text |Cite
|
Sign up to set email alerts
|

Introduction, production, and persistence of five grass species in dry hill country

Abstract: Grass species were rotary-hoe-drilled into hieracium-dominated fescut;! tussock. Late autumn and early spring herbage accumulation and composition were determined after three summer grazing treatments (0, 6, and 10 weeks freedom from grazing), and two pre-winter grazing managements. Subplots compared species production and persistence at two superphosphate (P) and three nitrogen (N) fertiliser levels. Over the 7 years, sown grasses only occasionally made significant contribution to the sward. 'Grasslands Apanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Although Apanui was more persistent at Tekapo than other grass species, it did show evidence of a decline in SG% after 7 years. Other cocksfoot varieties ('Grasslands Kara') showed evidence of better persistence at this site (Pollock & Scott 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Apanui was more persistent at Tekapo than other grass species, it did show evidence of a decline in SG% after 7 years. Other cocksfoot varieties ('Grasslands Kara') showed evidence of better persistence at this site (Pollock & Scott 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Grass species trials were conducted and reported separately in a co-ordinated programme at six sites throughout New Zealand-Fairplace, Southland (Stevens & Turner 1993); Lake Tekapo, Mackenzie Country (Pollock & Scott 1993); Carvossa, North Canterbury (Archie et al 1993); Rawhiti, Wairarapa ; Ballantrae, southern Hawkes Bay ; and Aratiatia, Taupo ). This paper draws conclusions from these trials and makes generalisations for the use of these species in dry hill country.…”
Section: Materials and Metiiodsmentioning
confidence: 99%
“…Previous studies have examined the effect of fertiliser on high-country soil properties as part of pasture development or revegetation (O'Connor 1962;Dunbar & Adams 1972;Davis 1981;Mclntosh et al 1984;Floate & Enright 1991;Pollock & Scott 1993;Svavarsdottir 1995;Boswell 1997). In New Zealand generally, interest has focussed on the P components of soils, both in relation to the distribution of natural vegetation, and for the development of legume-based pastures.…”
Section: Introductionmentioning
confidence: 99%
“…), Lake Tekapo on previously hieracium (Hieracium pilosella L.) infested fescue tussock (Festuca novae-zelandiae (Hack) Cockayne) grasslands and commenced in 1990. One block of the trial had been partially developed eight years previously with sod-seed drilling of different grass species with legumes and two annual superphosphate x three nitrogen fertiliser treatments [2]. That trial had been largely unsuccessful with a good early phase of alsike clover (T. hybridum L.) dominance but poor establishment of sown grasses.…”
Section: Methodsmentioning
confidence: 99%
“…Those treatments included: with or without a previous development legume dominant phase; sowing method (surface broadcast, disc drill, or experimental drill giving partial cultivation); prior herbicide treatment; use of starter nitrogen fertiliser; fertiliser placement in relation to seed; sowing season; grass species and accompanying legume species [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%